EFFECT OF FERTILIZATION AND WATERSTRESS ON DOWNY BROME (BROMUS TECTORUM) INFESTED WHEAT (TRITICUM AESTIVUM L.) GROWN UNDER CONTROLLED ENVIRONMENT (Biological Sciences - PJSIR, 2022)
Two greenhouse studies were undertaken in 1988 and 1989 at University of Wyoming, Laramie, USA to determinethe effects of N alone N + P placement methods on downy brome infested wheat grown in pots with normal irrigationand waterstress. Results of the first ex peri ment showed that blend of Nand P gave 20% more downy brome tillers thanan application of N only. Similarly, surface broadcasting of NP fertilizer produced greater tiller numbers (44%) and drymatter yield (28%) of downy brorne compared to the deep placement of the same nutrients. Deep banded NP fertilizershowed promise for greater plant height (13.6 em), ear length (2.9cm), grain yield (24%) and straw yield (26%) of wheatin comparison with surface broadcast application treatment. In second greenhouse study (J 989), water stressed andunstressed treatments differed significantly from each other in downy brome dry matter yield, wheat yield componentsand wheat dry matter production. Deep banding treatment, compared with broadcasting ofNP, afforded relatively lowerdowny brome dry matter yield and higher grain and dry matter yield of wheat.